2004
DOI: 10.1562/2004-04-23-ra-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of Various Quinolone Antibiotics in Aqueous–organic Solvent Mixtures¶

Abstract: The spectroscopic properties of enoxacin (ENO), oxolinic acid (OXO) and nalidixic acid (NAL) were studied in various H2O-CH3OH and H2O-CH3CN mixed solvents because these solvents were thought to behave as a biological mimetic system. ENO has piperazinyl group, but OXO and NAL do not have this substituent. The fluorescence emission spectra of ENO were very sensitive to the composition of the solvents. In the Lippert-Mataga analysis of the steady-state fluorescence data, clear reverse solvatochromism was exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The fluorescence quenching also has been found in some fluorate quinolones bearing the piperazinyl group when the solvent was changed from water to organic solvents (28,29). This has been attributed to a rapid nonradiative deactivation via intramolecular electron transfer from the piperazinyl to the fluoroquinolone ring in organic solvents (22,28). As proposed for several quinolones (6,7,29), the main species of PM existing in nonprotic solvents can be considered to be the intramolecularly hydrogen-bonded species, Ia in Scheme 2.…”
Section: Solvent Effect On the Photophysical Behaviormentioning
confidence: 85%
See 2 more Smart Citations
“…The fluorescence quenching also has been found in some fluorate quinolones bearing the piperazinyl group when the solvent was changed from water to organic solvents (28,29). This has been attributed to a rapid nonradiative deactivation via intramolecular electron transfer from the piperazinyl to the fluoroquinolone ring in organic solvents (22,28). As proposed for several quinolones (6,7,29), the main species of PM existing in nonprotic solvents can be considered to be the intramolecularly hydrogen-bonded species, Ia in Scheme 2.…”
Section: Solvent Effect On the Photophysical Behaviormentioning
confidence: 85%
“…These values show that U F for OX is almost invariant with the solvents. Park et al (28) also reported that U F for this compound is constant in wateracetonitrile and water-methanol mixtures.…”
Section: Solvent Effect On the Photophysical Behaviormentioning
confidence: 87%
See 1 more Smart Citation
“…In TFE the spectrum was blueshifted by 10 nm with respect to THF, suggesting that specific solute-solvent interactions in the singlet excited state occurs. The shift in the emission spectrum could be also interpreted in terms of a small difference between the dipole moments of the So and S1 states (12). On the other hand, the fluorescence quantum yields slightly decrease in protic solvents.…”
Section: Fluorescence Propertiesmentioning
confidence: 94%
“…In spite of the photosensitizing reaction associated to this drug, the photophysical behavior has received less attention. Fluorescence spectra and fluorescence quantum yields have been reported for NA and related compounds at some pH (3), and recently in some mixed solvents (12). Photophysical studies in different environments are of relevant importance because the regions where the drug can be localized differ drastically in polarity, and the polarity can influence the reactions responsible for NA phototoxicity.…”
Section: Introductionmentioning
confidence: 99%